Life experiences of boars can shape the survival, aggression, and nociception responses of their offspring - Sabei, Leandro; Bernardino, Thiago; Parada Sarmiento, Marisol; Barbosa, Bruna Stanigher; Farias, Sharacely de Souza; Ghantous, Giovana Fumes; de Lima, César Gonçalves; Poletto, Rosangela; Zanella, Adroaldo José (Frontiers in Animal Science, 2023)
Boars are often housed in stressful environments on commercial farms, experiencing poor welfare. These conditions may cause epigenetic changes in the boars’ gametes, which could potentially be transmitted to their offspring. We aimed to investigate the effect of three different boars housing environments on the survival, aggression, and nociceptive responses of their offspring. For four weeks, 18 boars were housed in three different systems: crates (C;n=6), pens (P;n=6), and enriched pens (E;n=6). The environmental enrichment was provided twice daily (brushing, shower, and hay). Thirteen gilts were housed in outdoor paddocks and inseminated with pooled semen from the boars kept in the three treatments. We evaluated the number of live-born, stillborn, and weaned piglets, sex, and mortality rate. Weaning was performed at 29 days of age. For each piglet, six body photographs were taken for five days postweaning to measure skin lesions (n=138). On Day 34, the nociceptive pressure threshold was assessed using an analgesimeter (n=138). DNA paternity tests were carried out at the end of the study (n=181). A generalized linear model with a negative binomial distribution was used to compare the number of live-born/weaned piglets and skin lesions among the treatment groups. We used a Kruskal‒Wallis test to analyze nociceptive data. More live-born and weaned piglets were fathered from boars kept in the E group than the P group (p=0.002;p=0.001, respectively). A trend was observed in the number of skin lesions on the left side of piglets (PE>C;p<0.001). Our results suggest that providing an enriched environment for boars can increase the number of live-born and weaned piglets. Moreover, the boars housing conditions can influence nociceptive threshold in their offspring. Further research must be performed to understand the underlying mechanism associated with these changes using epigenetics protocols and measuring physiological indicators and other molecular markers in semen and/or sperm cell samples.